ANALYSIS OF DIFFERENCES IN FINANCIAL PRODUCTIVITY AND PRIVATE BANKING USING VALUE ADDED METHODS - Purwantini, V. Titi; Brotojoyo, Endang (Sekolah Tinggi Ilmu Ekonomi AUB Surakarta)
AbstractThe purpose of this study is to obtain empirical evidence of differences in the productivity of banking finance listed on the Indonesia Stock Exchange using the Economic Value Aded method. The samples in this study were 4 government banks and 4 private banks listed on the Indonesia Stock Exchange from 2015 to 2018. The sampling technique was using the purposive sampling method, which is a private bank that gives dividends annually and local foreign exchange private banks. The data analysis technique consists of testing the normality and different paired sample testResearch results prove that based on the Difference Test Paired Sample Test with EVA method, the results show that there is no significant difference between government and private banks in the Value Added assessment Keywords: Financial Productivity, Economic Value Adedd